As iniciativas legiferantes compulsórias - Radi Junior, Jorge (2014)
The present work is mainly aimed to demonstrate the existence of compulsory legislative initiatives at the federal level, which force state(s) entity(ies) legitimated to present it at a given time, under penalty of accountability. The study focuses on the analysis of present Federal Constitution and begins with the investigation of state models adopted by the Federative Republic of Brazil, which resumes in federative form of medium-grade, self-controlled state, presidential system, democracy variable popular influence regimen and liberal republican form of short term governance. Because they are fundamental principles of the Brazilian state, these models greatly influence the rules of legislative initiatives. It was found that the legislative function in the Federal Constitution, equates to the law production, in the formal sense, and that is performed by all the Powers, but in main way, only by the Legislature. The drafting of the law is made by process, which, for teaching purposes, can be divided into phases, with an inaugural phase, called the initiative, in which is practiced the initiative-act (bill) from the exercise of initiative-competence. The rules of initiative-competence are exclusively settled in the Constitution, in an expressly and exhaustively manner. Although it has a particular structure, the rule of initiative-competence brings an common element of other competences, it is the duty-faculty, for which converge simultaneously the mandatory implementation of the rule (duty) and discretionary judgment to exercise (faculty). The mandatory implementation is raised by the existence of primary and/or secondary public interest, and the discretionary judgment derives from the political function. The combination duty-faculty guides the legitimated to implement initiative-competence. However, there are three sets of rules that, exceptionally, induce the duty and inhibit the faculty, turning compulsory execution the effect of the initiative-act, at the right term. The non-implement of initiative-competence in this given period, imply an omission unlawful act, and the improper implement of the rule results a commissive unlawful act. By practicing both acts, the legitimated may be liable